Morocco : Selected Issues. - International Monetary Fund. Middle East and Central Asia Dept. (Washington, D.C. : International Monetary Fund, 2013)
Morocco has made substantial progress in increasing inclusive growth over the past decade, but additional efforts in terms of growth-enhancing structural reforms are needed. Preserving economic efficiency and fostering growth while strengthening inclusiveness remains a priority. This paper describes the fuel subsidy system in Morocco, introduces an organizing framework to illustrate the trade-offs involved in meeting various economic and social objectives when considering subsidy reform, and highlights some lessons from the international experience in implementing subsidy reforms that may be pertinent to the case of Morocco.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet